PALEODOSIMETRIC PROPERTIES OF O2 3- CENTERS IN QUARTZ - Rakov L.T.; Moiseyev B.M. (My University, 1989)
Several minerals, including quartz, calcite and fluorite, have paleodosimetric properties, and methods of mineral prospecting and geological dating that make use of them have been developed. In the present paper we discuss the use of O23- hole centers in quartz in paleodosimetry. As indicated by electron paramagnetic resonance (EFR) data, they are caused by silica vacancies in the quartz lattice. The experimental work reported here was performed with an EPR spectroscope at a wavelength λ = 3 cm. The quartz was irradiated with gamma rays from 60Co. The concentration of O23- centers was determined after heating the quartz to 3000° C for 5 minutes in order to convert them to the paramagnetic state. O23- centers can be used like E1, D, and Al centers, to evaluate natural radiation doses received by quartz.